PEMANFAATAN KEONG TEMBERUNGUN (Telescopium-telescopium) SEBAGAI PAKAN ALTERNATIF TERHADAP PERTUMBUHAN DAN MOULTING KEPITING BAKAU (Scylla serrata) - Heppi Iromo, M.Si (Fakultas Perikanan Dan Ilmu Kelautan Universitas Borneo Tarakan, 2012)
Feeding with a balanced formulation of nutrition, can help the process of growth and moulting of mub crab,Scylla serrata. In general, the Soca crab aquaculture utilize feed that is still competitive with humans thereby increasing the cost operasional, while in the intensive aquaculture require the availability of feed in a number of good quality, inexpensive, sustainable and high production value. One of an alternative food for the growth of mud crab is temberungun snail (Telescopium-telescopium), which is a waste of traditional farming in ponds. This study aimed to compare the effect of temberungun snail as a feed with other feeds that high economic value for the growth and moulting of mud crab. The research was carried on January to May in traditional ponds in the small island of Tarakan. Four feed treatments were applied: A = trash fish, B = temberungun snails (Telescopium-telescopium), C = crustaceans (Penaeid sp), D = squid (Loligo sp). The results of the studi showed that the use of non-economical feed of temberungun snail was not significantly different with the other natural feed that high economic value to growth and moulting of mud crab. Keywords : Scylla serrata, growth, moulting, snail temberungun